Implementation of the multielectrode radiofrequency-balloon in real-world clinical practice—operator learning curve and procedural outcome at a high-volume center - Zylla, Maura M.; Starrach, Lydia; Rahm, Ann-Kathrin; Thomas, Dierk; Frey, Norbert; Lugenbiel, Patrick (Frontiers in Cardiovascular Medicine, 2023)
The novel multielectrode radiofrequency (RF) balloon catheter (HELIOSTAR TM .Biosense Webster) is a new technology for pulmonary vein isolation (PVI) in atrial fibrillation (AF), combining RF-ablation and 3D-mapping visualization with the concept of a "single-shot"ablation device. This study evaluates the operator learning curve und procedural outcome during implementation of the multielectrode RF-balloon at a high-volume center.The first 40 patients undergoing PVI by multielectrode RF-balloon catheter at Heidelberg University Hospital were included in this prospective study. Procedural outcome was analyzed over the course of increasing experience with the device.Results: 157/157 pulmonary veins (PVs) were successfully isolated with the RF-balloon catheter, in 73.2% by a single RF-application. Median time to isolation (TTI) was 11.0 sec (Q1=8.0 sec; Q3=13.8 sec). Median procedure time was 62.5 min (Q1=50.0 min; Q3=70.5 min). LA-dwell time was 28.5 min (Q1=23.3 min; Q3=36.5 min). Median fluoroscopy duration was 11.6 min (Q1=10.1 min; Q3=13.7 min). No serious procedure-related complications were observed, apart from one case of unclear, post-procedural acute-on-chronic kidney injury. With increasing operator experience, an additional reduction in procedure duration was observed.Rapid implementation of a "single shot"-ablation device combining RF-ablation and 3D-mapping can be achieved with high acute procedural efficacy and safety at a highvolume center. Previous experience with "single-shot" ablation devices may be advantageous for time-efficient introduction of the novel RF-balloon catheter into clinical practice.